Ag(I) camphorimine complexes with antimicrobial activity towards clinically important bacteria and species of the Candida genus. - João M S Cardoso; Soraia I Guerreiro; Andreia Lourenço; Marta M Alves; M Fátima Montemor; Nuno P Mira; Jorge H Leitão; M Fernanda N N Carvalho (PLoS ONE)
The present work follows a previous report describing the antibacterial activity of silver camphorimine complexes of general formula [Ag(NO3)L]. The synthesis and demonstration of the antifungal and antibacterial activity of three novel [Ag(NO3)L] complexes (named 1, 2 and 3) is herein demonstrated. This work also shows for the first time that the previously studied complexes (named 4 to 8) also exert antifungal activity. The antibacterial activity of complexes was evaluated against Staphylococcus aureus, Pseudomonas aeruginosa, Burkholderia contaminans and Escherichia coli strains, while antifungal activity was tested against the Candida species C. albicans, C. glabrata, C. parapsilosis and C. tropicalis. The antimicrobial activity of the complexes ranged from very high (complex 4) to moderate (complex 6) or low (complex 8), depending on the structural and electronic characteristics of the camphorimine ligands. Notably, the highest antibacterial and anti-Candida activities do not coincide in the same complex and in some cases they were even opposite, as is the case of complex 4 which exhibits a high anti-bacterial and low antifungal activity. These distinct results suggest that the complexes may have different mechanisms against prokaryotic and eukaryotic cells. The antifungal activity of the Ag(I) camphorimine complexes (in particular of complex 1) was found to be very high (MIC = 2 μg/mL) against C. parapsilosis, being also registered a prominent activity against C. tropicalis and C. glabrata. None of the tested compounds inhibited C. albicans growth, being this attributed to the ability of these yeast cells to mediate the formation of less toxic Ag nanoparticles, as confirmed by Scanning Electron Microscopy images. The high antibacterial and anti-Candida activities of the here studied camphorimine complexes, especially of complexes 1 and 7, suggests a potential therapeutic application for these compounds.